Kinerja Irigasi Tetes Tipe Emiter Aries Pada Tanaman Pisang Cavendhis Di Pt Nusantara Tropical Farm - Muhamad Idrus; Andre Velthuzend; Didik Kuswadi; Suprapto Suprapto; I Gde Darmaputra (Jurnal Penelitian Pertanian Terapan, 2018)
This research was conducted in PT Nusantara Tropical Farm ( PT NTF) at Jepara, Margosakti, Labuhan Ratu, East Lampung District.  The plants which were cultivated in PT NTF such as Cavendish banana, pineapple, crystal guava, and naga fruit. The irrigation being used to irrigated cavendish banana is drip irrigation method with Aries emitter type. Watering method of drip irrigation system that used for Cavendish banana is cross watering and block watering methods. The goals of this research were to determine the performance of drip irrigation line for Cavendish banana by using both kinds of watering method.  The performance indicator of irrigation system included the conveyance efficiency, the uniformity coefficient, the length time irrigation, and the amount of fuel consumption for diesel machine of a pump. The result of this research showed that the value of the conveyance efficiency of drip irrigation with cross watering method was 90,2% and 80,0% for block watering method. The uniformity coefficient on cross watering method was 87,55% and 97,10% for block watering method.  The amount of fuel consumption for 10,46 ha area with cross watering method was 29,49 l  and 40,52 l  for 10,2 ha area with block watering method.